1988
DOI: 10.21000/jasmr88010002
|View full text |Cite
|
Sign up to set email alerts
|

Use of Acid-Base Accounts in Premining Prediction of Acid Drainage Potential: A New Approach from Northern West Virginia

Abstract: Abstract.--Premining prediction· of postmining drainage quality is required by l~w, but the method most often used, involving acid-base accounting, was never intended to predict mine drainage quality and as used in the past has proven unreliable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…As indicated by others (Brady et al, 1994), MPA by itself is not the critical parameter for predicting post‐mining water quality, nor is it expected to be a reliable predictor. On the other hand, an NP of <20 was suggested by diPretoro and Rauch (1988) to produce acid drainage, while Brady et al (1994) indicated this value to be <10. Total NP in our study correlated with net alkalinity in post‐mining water on our 56 sites ( R 2 = 0.12, figure not shown), but the NP values used by these two former studies did not fit our data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As indicated by others (Brady et al, 1994), MPA by itself is not the critical parameter for predicting post‐mining water quality, nor is it expected to be a reliable predictor. On the other hand, an NP of <20 was suggested by diPretoro and Rauch (1988) to produce acid drainage, while Brady et al (1994) indicated this value to be <10. Total NP in our study correlated with net alkalinity in post‐mining water on our 56 sites ( R 2 = 0.12, figure not shown), but the NP values used by these two former studies did not fit our data.…”
Section: Resultsmentioning
confidence: 99%
“…Volumes of each layer in the overburden were determined in three ways. The first way (Ziem) was a right‐triangle method modified from diPretoro and Rauch (1988) The cross‐sectional area perpendicular to the highwall was calculated from depth and pit width. The cross‐sectional area of each layer was calculated by interpolation with layer depths and the average slope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ABA techniques have also been used by regulatory authorities and researchers to predict if mining would produce acidic or alkaline water quality (diPretoro and Rauch, 1988;Erickson and Hedin, 1988;Brady et al, 1990). The basic principal involves measurement of the concentration of total sulfur and total carbonate concentration, or neutralization potential in overburden rock and calculation of the calcium-carbonate deficiency (also known as the net-neutralization potential or NNP) for each sampling interval (Sobek et al, 1978).…”
Section: Acid-base Accountingmentioning
confidence: 99%
“…It is unrealistic to believe that these assumptions are correct in the natural environment and therefore many researchers have questioned the ability of ABA to accurately predict post-mining drainage quality (diPretoro and Rauch, 1988;Erickson and Hedin, 1988). In addition, there is uncertainty as to which ABA parameters most accurately estimate acid-or alkaline-production potential.…”
mentioning
confidence: 99%